Peningkatan Keterampilan Berpikir Kritis, Learning Ownership, dan Hasil Belajar Kognitif Melalui Model Oriented Guided Inquiry Learning - Himas Willya Putri Abdillah; Herawati Susilo (Universitas Negeri Jakarta, 2026)
The improvement of critical thinking, learning ownership, and cognitive learning outcomes has become highly urgent because they are essential foundations in shaping a generation that is adaptive, independent, and competent in supporting the realization of Indonesia Emas 2045. The POGIL offers practical guided inquiry activities to train critical thinking, enhance students' responsibility in learning process, and strengthen conceptual understanding. This research is designed to increase critical thinking, learning ownership, and cognitive learning outcomes by implementing the POGIL. A qualitative approach was employed in this research, utilizing a classroom-based action research method involving students of XI IPA 1 at SMAI Al-Ma'arif Singosari as research subjects. The results indicate that implementing the POGIL positively impacts critical thinking, learning ownership, and cognitive learning outcomes. Data on critical thinking skills show an improvement from moderate to high in the indicators of application, using data to develop critical perspectives, and analysis, meanwhile the increase from low to high occurred in the indicators of evaluating and synthesizing. Additionally, learning ownership improved, marked by the rise from low to moderate across all indicators reflecting their responsibility for the learning process. In the cognitive domain, the average score showed an improvement, with a classical completeness rate of 89.66%. These findings confirm the effectiveness of the POGIL in enhancing essential learning aspects for conceptual mastery and 21st-century skills. POGIL is more effective for concept understanding and problem-solving, thus it needs to be combined with media or technology to optimize its application across various types of learning materials.